Peran Five-Minute Meeting terhadap Target Output Bagian Sewing Line 34 di PT X - Widia Roker; Ary Kusmanto (Lembaga Pengembangan Kinerja Dosen, 2026)
The internship program is part of the implementation of the Independent Learning and Independent Campus (MBKM) policy, which aims to provide students with real-world work experience. This internship report was prepared to analyze the role of the Five-Minute Meeting in achieving output targets for Sewing Line 34 at PT X. The internship was conducted in the Sewing section, where the student worked as a sewing operator. Data collection techniques included direct observation, interviews, documentation, and literature review during the internship. Observations showed that before the routine implementation of the Five-Minute Meeting, production output on line 34 was around 450 units per day, compared to the target of 500 units per day. After the consistent implementation of the Five-Minute Meeting, production output reached and even exceeded the company's target. Based on these results, it can be concluded that the Five-Minute Meeting plays a significant role in improving employee understanding of work targets, employee motivation, and achieving production output for the Sewing section, particularly on line 34, at PT X.